Analysis of risk factors for prolonged postoperative chest tube drainage after uniportal video-assisted thoracoscopic surgery pulmonary resection - Weinian, Wu; Yongjun, Li (Frontiers in Surgery, 2026)
ObjectiveThis study aimed to identify independent risk factors for Prolonged Postoperative Chest Tube Drainage (PPCTD) in patients undergoing uniportal video-assisted thoracoscopic surgery (VATS) pulmonary resection.MethodsA retrospective observational cohort study was conducted involving 185 patients who underwent uniportal VATS pulmonary resection between January 2022 and December 2024. Patients were categorized into a prolonged drainage group (>7 days, n = 47) and a non-prolonged drainage group (≤7 days, n = 138) based on postoperative chest tube duration. Univariate and multivariate logistic regression analyses were performed to identify independent risk factors for PPCTD.ResultsMultivariate analysis identified five independent risk factors for PPCTD: deep nodule resection (OR = 6.625, 95% CI: 2.512–17.469, P = 0.004), preoperative FEV1% < 70% (OR = 5.590, 95% CI: 1.987–15.728, P = 0.005), use of ≥4 stapler cartridges (OR = 4.775, 95% CI: 1.689–13.498, P = 0.012), intraoperative blood loss ≥250 mL (OR = 4.064, 95% CI: 1.421–11.623, P = 0.024), and preoperative anemia (OR = 3.434, 95% CI: 1.152–10.238, P = 0.033). A combined predictive model incorporating these factors demonstrated excellent discriminative ability (AUC = 0.892).ConclusionDeep nodule resection, impaired pulmonary function (FEV1% < 70%), extensive stapler use (≥4 cartridges), significant intraoperative blood loss (≥250 mL), and preoperative anemia are significant independent risk factors for PPCTD following uniportal VATS pulmonary resection. These findings highlight potential targets for preoperative optimization and refined surgical technique. However, the derived predictive model requires external validation in independent cohorts before it can be considered for routine clinical use.